2018
DOI: 10.1111/bjd.16399
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in zoster disease burden: a population-based cohort study to identify social determinants using linked data from the U.K. Clinical Practice Research Datalink

Abstract: SummaryBackgroundZoster vaccination was introduced in England in 2013, where tackling health inequalities is a statutory requirement. However, specific population groups with higher zoster burden remain largely unidentified.ObjectivesTo evaluate health inequalities in zoster disease burden prior to zoster vaccine introduction in England.MethodsThis population‐based cohort study used anonymized U.K. primary care data linked to hospitalization and deprivation data. Individuals aged ≥ 65 years without prior zoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…This study demonstrates that in a public funded healthcare system, vaccination inequalities exist during a crucial period of programme initiation, and identifies socio-demographic groups that could be targeted with tailored interventions to increase zoster vaccine uptake. Of particular interest is the finding of lower uptake among care home residents; we have shown recently that individuals in care homes are at higher risk of developing zoster,[ 49 ] and so are a group with possible double health inequity (of both zoster burden and zoster vaccine uptake). Lower vaccine uptake among these residents could be due to lack of awareness amongst care home staff about the newly introduced programme and issues around getting consent.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrates that in a public funded healthcare system, vaccination inequalities exist during a crucial period of programme initiation, and identifies socio-demographic groups that could be targeted with tailored interventions to increase zoster vaccine uptake. Of particular interest is the finding of lower uptake among care home residents; we have shown recently that individuals in care homes are at higher risk of developing zoster,[ 49 ] and so are a group with possible double health inequity (of both zoster burden and zoster vaccine uptake). Lower vaccine uptake among these residents could be due to lack of awareness amongst care home staff about the newly introduced programme and issues around getting consent.…”
Section: Discussionmentioning
confidence: 99%
“…We thus included age, sex, and various immunosuppressive treatments, and chronic conditions ( 2 , 26 ), including rheumatoid arthritis, systemic or subacute lupus erythematosus, inflammatory bowel disease, chronic kidney disease, asthma, chronic obstructive pulmonary disease, use of inhaled glucocorticoids, diabetes mellitus, hospital-diagnosed mood disorders, and severe immunosuppression (e.g., human immunodeficiency virus infection, hematopoietic stem cell transplantation, other cellular immune deficiency, leukemia, lymphoma, myeloma, use of oral glucocorticoids or other immunosuppressant drugs). We also identified the highest level of education achieved by each person (as a measure of socioeconomic status, which could affect lifestyle habits and health-seeking behavior ( 29 )) and country of origin as proxy for ethnicity (associated with zoster ( 29 ) and potentially linked to lifestyle through socioeconomic or other factors).…”
Section: Methodsmentioning
confidence: 99%
“…The characteristics of the 69 individual studies are provided in Table 1. The majority of studies were conducted in the United States of America (USA; n = 14), 6,15-27 followed by Canada (n = 6), [28][29][30][31][32][33] the United Kingdom (UK; n = 6), [34][35][36][37][38][39] Germany (n = 5), [40][41][42][43][44] Japan (n = 5), [45][46][47][48][49] the Netherlands (n = 5), 36,[50][51][52][53] Spain (n=5), [54][55][56][57][58] Taiwan (n = 4), [59][60][61][62] Australia (n = 3), [63][64][65] China (n = 3), [66][67][68] Italy (n = 3), [69][70][71] France (n = 2), 72,73 New Zealand(n = 2),…”
Section: Study Characteristicsmentioning
confidence: 99%
“…While 6 studies gave only one overall HZ incidence (Table 1), 58 studies stratified the incidence by age (Table 1), 33 studies by gender (Table 1), 23 studies by study year (Table 1), and 4 studies by ethnicity. 15,17,21,38 In 5 studies, the HZ incidence was reported for the overall general population as well as the immunocompetent population only. 6,21,24,41,71 Lastly, 3 studies reported the HZ incidence for two different case definitions of HZ.…”
Section: Study Characteristicsmentioning
confidence: 99%